Timesheet Management System: A Case Study of SCI Professional Service Company Limited - Sungtong, Badee; Srithammasak, Boonchuay (Journal of Advanced Development in Engineering and Science, 2023)
The purpose of this study aims to develop a timesheet management system of SCI Professional Service Co., Ltd. This study is conducted in accordance with the system development methodology. The system is designed and modelled using the principles of the system development life cycle and object-oriented approaches with UML. Web applications are implemented. The researcher surveys the satisfaction of using the system from the sample group managers of 33 people, which results in the satisfaction assessment are very good. The developed system can reduce redundancy and help to manage timesheets with efficiency and flexibility.